Religious Court Legal Policy on Early Marriage Warning: An Analysis of the Implementation of Supreme Court Regulation Number 5 of 2019 - Mu'minin, Anwarul (Perkumpulan Dosen Tarbiyah Islam, Indonesia, 2025)
This study aims to analyze the implementation of Supreme Court Regulation (PERMA) No. 5 of 2019 as a judicial policy designed to tighten the marriage dispensation mechanism in order to prevent child marriage. The research employs a qualitative approach with normative juridical and structural perspectives to examine how the regulation is applied in judicial practice. Data were analyzed by assessing the consistency between the normative provisions of PERMA and their practical enforcement, particularly in relation to the principle of the best interests of the child, encompassing psychological, health, and educational considerations. The findings reveal that the implementation of PERMA No. 5 of 2019 has not yet been fully optimal. Although the regulation provides a clear normative framework requiring judges to apply stricter standards in assessing marriage dispensation requests, its effectiveness is constrained by several factors. These include limited public awareness of the heightened legal requirements, insufficient dissemination of information regarding the regulation, and institutional capacity challenges within the judicial system. As a result, the regulation’s intended objective of reducing child marriage has not been achieved to its full potential. This study argues that strengthening the effectiveness of PERMA requires comprehensive public legal education, enhancement of internal judicial capacity, and improved inter-sectoral coordination among courts, educational institutions, and social welfare agencies. These measures are essential to ensure that the regulation functions not merely as a formal legal instrument, but as an effective mechanism for child protection within the judicial process.